Balancing the rights and duties of European and national citizens: A democratic approach - Bellamy, R; Lacey, J (Taylor and Francis, 2018)
How should we conceive of the relationship between European citizenship and national citizenship from a normative perspective? While the Treaties assert the supplementary nature of European citizenship vis-à-vis national citizenship, advocates of trans- and supra-national citizenship perspectives have agreed with the European Court of Justice that Union citizenship will ultimately supplant or subsume national citizenship. By contrast, we draw upon demoicratic and stakeholder citizenship theories to defend the primacy of national over European citizenship. Taking the cases of political and welfare rights, we argue that member states may have special duties to second-country nationals stemming from a European social contract, but that these duties must be balanced against the rights and duties of national citizens stemming from the national social contract.